Bitter melon fruit extract has a hypoglycemic effect and reduces hepatic lipid accumulation in ob/ob mice. (17th December 2019) - Dwijayanti, Dinia R.; Shimada, Takumi; Ishii, Toshinari; Okuyama, Tetsuya; Ikeya, Yukinobu; Mukai, Eri; Nishizawa, Mikio
Abstract : Bitter melon ( Momordica charantia L.) is a vegetable and has been used as traditional medicine. Recently, we reported that bitter melon fruit extracts and its ethyl acetate (EtOAc)‐soluble fraction markedly suppressed the expression of proinflammatory genes, including the inducible nitric oxide synthase gene. However, it is unclear whether bitter melon exhibits antidiabetic effects. In this study, we showed that cucurbitacin B, a cucurbitane‐type triterpenoid, was present in an EtOAc‐soluble fraction and suppressed nitric oxide production in hepatocytes. When the EtOAc‐soluble fraction was administered for 7 days to ob / ob mice, a type 2 diabetes mellitus model, the mice fed with this fraction exhibited a significant decrease in body weight and blood glucose concentrations compared with the mice fed without the fraction. The administration of the fraction resulted in significant increases in serum insulin concentrations and the levels of both insulin receptor mRNA and protein in the ob / ob mouse liver. The EtOAc‐soluble fraction decreased the interleukin‐1β mRNA expression, as well as hepatic lipid accumulation in hepatocytes. Taken together, these results indicate that administration of an EtOAc‐soluble fraction improved hyperglycemia and hepatic steatosis, suggesting that this fraction may be responsible for both the antidiabetic and anti‐inflammatory effects of bitter melon fruit.